Incidence of acute kidney injury in critically ill patients with COVID-19 and 90-day survival: Retrospective Cohort of a Public Intensive Care Unit, Joinville/Brazil - Aguiar, Fernanda Perito de (2023)
About one third of patients with COVID-19 in intensive care units (ICU) have acute kidney injury (AKI) requiring dialysis. Few studies have evaluated the survival ratel of patients with AKI in exclusively public ICUs. The aim of this study was to evaluate the 90-day in-hospital survival of patients with and without AKI requiring dialysis hospitalized with severe COVID-19. This is a historical cohort of a general hospital in Joinville, Santa Catarina/Brazil. All patients admitted to the ICU between March and December of 2020 with a confirmed diagnosis of COVID-19 were included. AKI was defined by the presence of acute renal function alteration requiring hemodialysis. A multivariate Cox regression model was used to assess the survival of patients with and without AKI requiring dialysis. The results of the study showed that, of the 187 patients included (55.5% men) with a mean age of 62.8±13.6 years, 37.4% had AKI requiring dialysis. Patients with AKI requiring dialysis used more vasoactive drugs, had greater severity on admission and higher mortality rate (84.3% vs. 63.2%; p=0.002) compared to those without AKI. The risk of death in patients with AKI was higher (crude RR= 1.60; 95% CI 1.13-2.26; p= 0.007). After adjustments for age, sex, comorbidities and clinical severity, the presence of AKI requiring dialysis remained associated with a higher frequency of 90-day mortality (RR= 1.49; 95% CI 1.03-2.15; p=0.032). The survival of patients with severe COVID-19 and AKI requiring dialysis in the studied sample was lower compared to private ICUs in Brazil, which suggests inequalities in the public system.